2012
DOI: 10.1029/2012ja017716
|View full text |Cite
|
Sign up to set email alerts
|

Recovery phase of magnetic storms induced by different interplanetary drivers

Abstract: [1] Statistical analysis of Dst behavior during recovery phase of magnetic storms induced by different types of interplanetary drivers is made on the basis of OMNI data in period 1976-2000. We study storms induced by ICMEs (including magnetic clouds (MC) and Ejecta) and both types of compressed regions: corotating interaction regions (CIR) and Sheaths. The shortest, moderate and longest durations of recovery phase are observed in ICME-, CIR-, and Sheath-induced storms, respectively. Recovery phases of strong (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…This paper is a continuation of our previous paper [Yermolaev et al, 2012b], and we use the same databases (OMNI data of interplanetary plasma and magnetic field parameters (see http://omniweb.gsfc.nasa.gov) [King and Papitashvili, 2004] and measurements of Dst index (see http://wdc.kugi.kyoto-u.ac.jp/index.html for the period of 1976-2000)) and the same method of classification of large-scale solar wind streams (see our catalog of large-scale interplanetary events for 1976-2000 on the web site ftp://www.iki.rssi.ru/pub/ omni [Yermolaev et al, 2009]). We analyze separately 798 moderate (with −100nT < Dst min ≤ −50 nT) and strong (Dst min ≤ −100 nT) magnetic storms.…”
Section: Methodsmentioning
confidence: 80%
See 4 more Smart Citations
“…This paper is a continuation of our previous paper [Yermolaev et al, 2012b], and we use the same databases (OMNI data of interplanetary plasma and magnetic field parameters (see http://omniweb.gsfc.nasa.gov) [King and Papitashvili, 2004] and measurements of Dst index (see http://wdc.kugi.kyoto-u.ac.jp/index.html for the period of 1976-2000)) and the same method of classification of large-scale solar wind streams (see our catalog of large-scale interplanetary events for 1976-2000 on the web site ftp://www.iki.rssi.ru/pub/ omni [Yermolaev et al, 2009]). We analyze separately 798 moderate (with −100nT < Dst min ≤ −50 nT) and strong (Dst min ≤ −100 nT) magnetic storms.…”
Section: Methodsmentioning
confidence: 80%
“…Our analysis showed that during this period, CIR, Sheath, MC, and Ejecta generated 145, 96, 62, and 161 magnetic storms, respectively. The interplanetary sources of the other 334 magnetic storms are indeterminate because of data gaps (indicated here as IND-induced storms) [Yermolaev et al, 2009[Yermolaev et al, , 2010[Yermolaev et al, , 2012a[Yermolaev et al, , 2012b. About 25% of the storms were multistep ones during their main and recovery phases, and these storms were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations